2021
DOI: 10.1080/21655979.2021.1966351
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LUCAT1 inhibits myocardial oxidative stress and apoptosis after myocardial infarction via targeting microRNA-181a-5p

Abstract: This study hoped to explore the effects and mechanism of long non-coding RNA (lncRNA) LUCAT1 regulating microRNA-181a-5p (miR-181a-5p) on oxidative stress and apoptosis of cardiomyocytes induced by H 2 O 2 . Totally, 72 patients with acute myocardial infarction (AMI) were included. H9c2 cardiomyocytes were cultured in vitro, and the H 2 O 2 model of cardiomyocytes was established. The expression levels of LUCAT1 and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Zhang et al demonstrated that the inhibition of death-associated protein kinase 1 (DAPK1) expression inhibited inflammation and oxidative stress and protected rats from myocardial injury caused by myocardial infarction [ 55 ]. In addition, a study by Xiao et al showed that the overexpression of lung cancer associated transcript 1 (LUCAT1) has a protective effect on AMI by inhibiting the effects of H 2 O 2 on oxidative stress, inflammation, viability, and apoptosis in H9c2 cells [ 56 ]. Therefore, we speculate that inhibiting the expression of S100A12 could inhibit oxidative stress and inflammation, thereby exerting a similar cardioprotective effect and reducing myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that the inhibition of death-associated protein kinase 1 (DAPK1) expression inhibited inflammation and oxidative stress and protected rats from myocardial injury caused by myocardial infarction [ 55 ]. In addition, a study by Xiao et al showed that the overexpression of lung cancer associated transcript 1 (LUCAT1) has a protective effect on AMI by inhibiting the effects of H 2 O 2 on oxidative stress, inflammation, viability, and apoptosis in H9c2 cells [ 56 ]. Therefore, we speculate that inhibiting the expression of S100A12 could inhibit oxidative stress and inflammation, thereby exerting a similar cardioprotective effect and reducing myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction is a common and serious clinical disease and a threat to public health worldwide in the future and tissue damage caused by myocardial ischemia is an important cause of fatal diseases [ 22 , 23 ]. In the present study, the protective effects of Oxycodone on myocardial I/R injury were investigated in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have demonstrated that high levels of miR-181 lead to the inhibition of myocardial inflammation via the modulation of pro-inflammatory markers (such as tumor necrosis factor-α (TNF-α) and IL-1β) and oxidative stress; through the regulation of ROS components such as SOD1 (superoxide dismutase 1) and SOD2; and by targeting ATF2 (activating transcription factor 2) ( Figure 1 ) [ 38 , 39 ]. Moreover, LUCAT1 and MIAT lncRNAs are regulators of miR-181a-5p, thereby modulating inflammation (TNF-α, IL6, and IL1β), oxidative stress (SOD levels), apoptosis, and cell viability in vitro, which was demonstrated in an in vitro model of CM injury or ischemia–reperfusion, as well as in vivo by modulating the JAK/STAT signaling pathway ( Figure 1 ) [ 40 , 41 ].…”
Section: The Emerging Impact Of Non-coding Rnas’ Regulation Of Cardia...mentioning
confidence: 99%
“…In this context, several lncRNAs can modulate miRNAs and play essential roles in cardiac inflammation, such as KCNQ1OT1 lncRNA, which sponges miR-130 and thus modulates ZNF91 (zinc finger protein 91), and Lucat1 lncRNA, which sponges miR-181. However, the molecular mechanisms relating them to cardiac inflammation remain largely elusive [ 40 , 83 ]. Additionally, other lncRNAs modulating miRNAs have emerging roles in cardiac inflammation, such as HULC lncRNA, which modulates the expression of miR-29 and miR-377, leading to the regulation of the NLRP3/Caspase-1/IL-1β signaling pathway, while TTTY15 lncRNA modulates miR-98 and, thereafter, CRP expression [ 192 , 194 , 195 ].…”
Section: Lncrnas In Cardiac Infarction and Regenerationmentioning
confidence: 99%